Molecular phylogenetics, diversification, and systematics of Tibicen Latreille 1825 and allied cicadas of the tribe Cryptotympanini, with three new genera and emphasis on species from the USA and Canada(Hemiptera: Auchenorrhyncha: Cicadidae) - Hill, Kathy B. R.; Marshall, David C.; Moulds, Maxwell S.; Simon, Chris (Zootaxa, 2015)
North America has a diverse cicada fauna with multiple genera from all three Cicadidae subfamilies, yet molecular phylogenetic analyses have been completed only for the well-studied periodical cicadas (Magicicada Davis). The genus Tibicen Latreille, a large group of charismatic species, is in need of such work because morphological patterns suggest multiple groups with complicated relationships to other genera in the tribe Cryptotympanini. In this paper we present a molecular phylogenetic analysis, based on mitochondrial and nuclear DNA, of 35 of the 38 extant USA species and subspecies of the genus Tibicen together with their North American tribal allies (Cornuplura Davis, Cacama Davis), selected Tibicen species from Eurasia, and representatives of other Eurasian and Pacific cryptotympanine genera. This tree shows that Tibicen contains several well-supported clades, one predominating in eastern and central North America and related to Cryptotympana Stål and Raiateana Boulard, another in western North America related to Cacama and Cornuplura, and at least two clades in Eurasia. We also present a morphological cladistic analysis of Tibicen and its close allies based on 27 characters. Character states identified in the cladistic analysis define three new genera, two for North American taxa (Hadoa gen. n. and Neotibicen gen. n.) including several Mexican species, and one for Asian species (Subsolanus gen. n.). Using relaxed molecular clocks and literature-derived mtDNA rate estimates, we estimate the timeframe of diversification of Tibicen clades and find that intergeneric divergence has occurred since the late Eocene, with most extant species within the former Tibicen originating after the mid-Miocene. We review patterns of ecology, behavior, and geography among Tibicen clades in light of the phylogenetic results and note that the study of these insects is still in its early stages. Some Mexican species formerly placed in Tibicen are here transferred to Diceroprocta, following refinement of the definition of that genus.